Practical Analysis of Field Experiences: Studies on Prospective Early Childhood Education Teachers - Mukminin, Amirul; Hasjiandito, Akaat; Widhanarto, Ghanis Putra (Journal of Nonformal Education, 2020)
The implementation of PPL is carried out by students of educational programs in Indonesia. This research aims to determine student performance in implementing PPL in the PGPAUD Study Program and determine the inhibiting and supporting factors of implementation PPL of PGPAUD students. This research was conducted based on a quantitative line of thought. Even so, technically, qualitative methods cannot be abandoned, especially concerning the importance of the study results' versatility. The subjects of this study were school principals and tutors of partner schools in Central Java Province. Data will be collected in two ways, namely a questionnaire in the form of a subject's self-response to statements made based on the PPL implementation assessment module's indicators. The implementation of learning can be described as 12.8% of respondents believe that students are in an outstanding category, 49.8% of respondents think that students are in a suitable type. There are 37.4% of respondents who say that they are not right. Inhibiting factors for PPL implementation for PGPAUD students include the practitioner's ability to establish a social relationship with the school community. Meanwhile, the factors that support the implementation of PPL for PGPAUD students include the location of PPL places that are close to the campus, the majority of PGPAUD lecturers are still young, online assessment and monitoring systems, good relations between partner schools and PGPAUD majors, internship programs 1 and 2 and field observations of subjects. PPL is designed jointly between the PGPAUD department and partner schools, so that it will run effectively.